Keeping obesity status is a risk factor of hypertension onset: evidence from a community-based longitudinal cohort study in North China - Cai, Qiujing; Zhao, Xiaolei; Dong, Liguang; Zhang, Xinmin; Wang, Chenglong; Wang, Shu; Zhou, Yi; Zhou, Xianliang; Li, Yanqi; Wang, Shuyu; Liu, Lisheng; Hu, Aihua (Frontiers in Public Health, 2023)
Objective: The purpose of our study was to investigate the association of obesity status change with hypertension onset based on a community-based longitudinal cohort study in north China. Methods: This longitudinal study included 3581 individuals free of hypertension at baseline in the first survey (2011-2012). All participants were followed (2018-2019). According to the criteria, a total of 2618 individuals were collected for analysis. We used adjusted Cox regression models and Kaplan-Meier survival analysis to estimate the association between obesity status change and hypertension onset. Additionally, we applied the forest plot to visualize the subgroup analysis including age, gender, and the differences in some variables between baseline and follow-up. Finally, we conducted a sensitivity analysis to examine the stability of our results. Results: Over nearly 7 years of follow-up, a total of 811 (31%) developed hypertension. The new hypertension incidence was mostly observed in those who were keeping obese all the time (P for trend < 0.01). In the fully adjusted Cox regression model, keeping obese all the time would have a 30.10% elevated risk of future hypertension [HR 4.01 (95% CI 2.20-7.32)]. The Kaplan-Meier survival analysis revealed the change in obesity status as an important feature to predict the occurrence of hypertension. Sensitivity analysis shows a consistent trend between the change in obesity status and hypertension onset in all populations. Subgroup analysis showed that age above 60 years was an important risk factor for hypertension onset, that men were more likely to develop hypertension than women, and that weight control had a beneficial effect on avoiding future hypertension for women. There were statistically significant differences in ∆BMI, ∆SBP, ∆DBP, and ∆baPWV between the 4 groups, and all variables except baPWV changes increased the risk of future hypertension. Conclusion: Our study shows that keeping obese status was notably associated with a significant risk of hypertension onset among the Chinese community-based cohort.